Barefoot banking the story behind the New Rural Bank of San Leonardo. (the Bank, 2003)
Presents the history of the New Rural Bank of San Leonardo in Nueva Ecija, Philippines and some examples of small entrepreneurs that the bank has helped with its "Lima para sa lahat" lending program.